Estrategias de marketing digital para la “Despensa Byrito” del cantón La Maná provincia de Cotopaxi. - Gallo Guato, Jonathan Vinicio (2023)
The objective of this research project is to propose digital marketing strategies for "Despensa Byrito " located in La Maná canton, because it would help to generate great value and well-being towards its clients. That is why the present investigation shows interest in positioning the brand of “Despensa Byrito " by ensuring customer’ loyalty and therefore increase sales through the proposal of digital marketing strategies. For this reason a mixed methodology with a qualitative and quantitative approach is used, supported by types of descriptive, exploratory, and applied research, and the information collection techniques such as the interview applied to the owner and the surveys applied to the community of the canton, whose population were the inhabitants of the canton La Maná. So that, a total number of 267 people were questioned by using the sampling formula, with a questionnaire to achieve and conclude with the data collected in the investigation and reach satisfactory conclusions that allows to make correct decisions in the marketing area of the company. For the data processing, descriptive statistics with Excel programs were executed, so the information obtained was interpreted according to the results of the applied surveys, in addition a content plan was established to launch monthly advertising campaigns through their social networks and do not discard the implementation of a web page, with attractive content. Among the results it is evident that 32.58% consider WhatsApp as one of the most relevant platforms that exist today, 31.84% believe that Facebook, 22.47% believe Instagram is one of the most relevant platforms and 13.11% remaining consider TikTok. This indicates that the most relevant platforms today are Facebook and WhatsApp